Aplicação do CAPM condicional ao mercado acionário brasileiro - Garcia, Paulo Renato Marchese (2015)
This study aims to empirically test the model of the conditional CAPM in the Brazilian stock market. The analysis is developed through theoretical exposition of the main causes that built the capital asset pricing model and the conditions under which it has been tested and developed. For this purpose, we used a sample of financial assets extracted from Economática system. After that six portfolios were formed based on financial literature assumptions in order to calculate the excess of return in each case. Following the procedure an econometric model was tested and adjusted to be possible its application apply the CAPM conditional version into Brazilian stocks market. Finally, the process was validated given the metrics presented in econometric results being robust and corroborating with the literature